(3QeGM MRH GdQMje Ydi fMhQ MRH GdQMjes - (3YeQ Hf SYjO GdehJj GdWhQj GdcOhj GdJjLGfj GdeZQHj, CHh LYaQ,J (B1261 (3g` s ((3eMeO Hf SOGJ Hf CMeO Hf SO GdCejf Hf GdMGL CHj HcQ Hf GdMGL YjSi s)
(3ChdgG (B:s
(3CeG HYO ,ajbhd gPG cJGH SejJg hVYI dfaSi hdENhGJi ai GdWQjbI hQJHJg Ydi ebOeI hNeSI hNeSjf aUdoG hNGJeI s
(3BNQgG (B:s
(3GdNGJei fSCd Gddg JYGdi MSfgG ai HjGf TQa GdPcQ Ydi ZjQg ef SGFQ GdWGYGJ hJe s
(3HgG fXGe GdJYbjHIs
(3cJHgG fGSNgG dTjNI YHO GdQMef GdeYQha HGHfhi Hf HGH CMeO Hf eMeO Hhis
(3fSNI ebQhAI heUMMI s
(3HYV YHGQGJgG HGdMeQI s
(3MhGagG eJBcdI s
(3bQf GdfSN (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs